Underpotential Deposition of Al-Ce Alloys at an Al Electrode from LiCl-KCl-CeCl3 Melts. Issue 8 (August 2016) - Meng, Zhang; Yunna, Li; Wei, Han; Milin, Zhang; Yun, Xue; Yanli, Wang; Yang, Gao
Abstract: Electrochemical behavior of Ce(III) and underpotential deposition of Al-Ce alloys were investigated at an Al active electrode in LiCl-KCl-CeCl3 melts. Compared with the cyclic voltammetry curves on a Mo electrode, the redox potential of Ce(III)/Ce at the Al electrode is more positive; there are two new plateaus between the deposition plateau of Al and Ce metal by open circuit chronopotentiometry, which means two kinds of intermetallic compounds. All above show Ce(III) forms intermetallic compound by underpotential deposition electrochemically. Furthermore, it is also confirmed by Al-Ce alloys, which are obtained at the Al active electrode in LiCl-KCl-CeCl3 melts after potentiostatic deposition under the same condition. The formation of AlCe and AlCe3 is illuminated by X-ray diffraction (XRD). The reasons of AlCe and AlCe3 formation were explained by XRD and phase diagram of Al-Ce. The standard Gibbs free energies of AlCe and AlCe3 formation were calculated by XRD and open circuit chronopotentiometry. The analysis of scanning electron microscopy (SEM) and energy dispersive spectrometry (EDS) reveals that cerium exists at the surface of Al electrode to form an Al-Ce alloys layer, which is about 28 μm in thickness, and evenly coated the Al electrode.